Synthesis and structure of some new Schiff bases, derivatives of 2-((4-((R-benzylidene)amino)-5-(2-fluorophenyl)-4H-1,2,4-triazole-3-yl)thio)acetohydrazides - Ye. S. Pruglo (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Triazole derivatives are among wide range of pharmacological agents, such as antimicrobial, analgesic, anti-inflammatory, anticonvulsant, antitumor, antimalarial, antiviral, antiproliferative, anti-cancer drugs etc. The importance of triazole derivatives is in their various biological properties. That is why they have a good position in heterocyclic chemistry.